Achieving Parity of Esteem of Mental Healthcare in the UK - Y. Sheikh; D. Gakhar; M.-H. Asunramu; H. Low; H. Yassin; K. Muthukumar (European Psychiatry, 2022)
Introduction Mental illness is the single largest cause of disability in the UK, with one in four individuals suffering from a mental health problem. Despite this, only 13% of the NHS budget goes towards treatment of mental illness. It is thus unsurprising that addressing the parity of esteem of mental health has been highlighted as a major priority for the healthcare system, with the NHS Five Year Forward plan aiming to achieve this by 2020.